Reakcje katolików w Niemczech i w Polsce na udział papieża Franciszka w rozpoczęciu obchodów 500-lecia reformacji w Szwecji - Kucharska-Dreiß, Elżbieta; Przyczyna, Wiesław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
Pope Francis’ visit to Sweden and his participation in the inauguration of the 500th anniversary of the Reformation triggered numerous reactions, both among German and Polish Catholics. The paper is an attempt to compare these reactions based on texts posted on selected Catholic websites: www.katholisch.de, www.domradio.de, www. kath.de, www.opoka.org.pl, www.deon.pl and www.fronda.pl. The analysis focuses on the following aspects: why the Pope went to Sweden; what and how he celebrated there. In general, German websites demonstrate largely similar stances and opinions formulated on the grounds of openness, kindness and mutual respect whereas opinions on Polish websites are clearly diverse: from liberal ones to the unambiguously conservative ones.